Up At Dawn - Zada, John; Rowntree, David (Canada, 2000)
Soros Documentary Fund Focusing on child labor in Egypt the film shows children as young as seven working in carpet factories, crafts workshops, printing plants, and in agriculture, tilling the fields for long hours. Several spokesmen for organizations which employ the children argue for the benefits of giving children a trade so that they can contribute to their families and ultimately have a career. The film explores the boundaries between vocational training and child labor.